On D0L systems with finite axiom sets - Honkala, Juha (Acta Cybernetica, 2003)
We give a new solution for the language equivalence problem of D0L systems with finite axiom sets by using the decidability of the equivalence problem of finite valued transducers on HDT0L languages proved by Culik II and Karhumäki.